LECTOTYPIFICATION AND AMENDED DESCRIPTION OF PHYLLANTHUS (PHYLLANTHACEAE) SPECIES DESCRIBED BY KOORDERS FROM SULAWESI, INDONESIA - Bouman, Roderick W; Ke?ler, Paul J.A.; Welzen, Peter C. van (REINWARDTIA, 2019)
BOUMAN, R. W., KEßLER, P. J. A. & VAN WELZEN, P. C. 2019. Lectotypification and amended description of Phyllanthus (Phyllanthaceae) species described by Koorders from Sulawesi, Indonesia. Reinwardtia 18(2): 97?103. ? Two species of Phyllanthus collected and described by Koorders during his travels on the island of Sulawesi (Indonesia) are lectotypified, descriptions amended and their taxonomic affinity is discussed. Phyllanthus mindorensis was found to be too similar to P. celebicus and is placed in the synonymy of the latter. A key is provided to the species of Phyllanthus on Sulawesi.